Encephalomyelitis associated with rheumatoid arthritis: a case report - Acewicz, Albert; Wierzba-Bobrowicz, Teresa; Michałowski, Łukasz; Pęcak, Mariola; Tarka, Sylwia; Chutorański, Dominik; Stępień, Tomasz; Felczak, Paulina; Sklinda, Katarzyna; Nasierowska-Guttmejer, Anna; Dorobek, Małgorzata (Folia Neuropathologica, 2021)
Encephalitis/encephalomyelitis in the course of rheumatoid arthritis (RA) remains a matter of debate. We present a case of a patient with encephalomyelitis associated with RA confirmed with post-mortem neuropathological examination. A 68-year-old woman with a long-standing, seropositive history of RA presented progressive disturbances of consciousness. Magnetic resonance imaging (MRI) of the brain and cervical spine revealed an increase of signal intensity on T2-weighted and fluid attenuated inversion recovery (FLAIR) images with corresponding restricted diffusion involving cerebral peduncles, pons, medulla oblongata, and cervical spinal cord and mild contrast-enhancement of the right cerebral peduncle. Extensive radiological and laboratory testing, including autoantibodies to paraneoplastic anti-neuronal and neuronal cell surface antigens, were all negative except for elevated rheumatoid factor. Cerebrospinal fluid (CSF) analysis revealed moderate pleocytosis with mononuclear cell predominance, mildly increased protein level, and negative viral PCRs, bacterial cultures, flow cytometry, and neuronal surface antibodies. Despite intensive treatment with corticosteroids, antibiotics, antiviral drugs, and intravenous immunoglobulin the patient died after 3 months of hospitalization. Post-mortem neuropathological examination revealed numerous, disseminated, heterochronous ischaemic lesions, rarely with haemorrhagic transformation, predominantly in the brainstem, and widespread, diffuse microglia and T-cell infiltrations with neuronal loss and astrogliosis, most severe in the frontal and temporal lobes. Mild, perivascular lymphocyte T infiltrations involved particularly small and medium-sized vessels and were associated with brainstem ischaemic lesions. The neuropathological picture confirmed diagnosis of encephalomyelitis, which together with the clinical course suggested association with RA. Concluding, encephalomyelitis due to RA remains a challenging, controversial entity that needs further research and the establishment of effective diagnostic and treatment guidelines.